THE NECESSITY OF CREATING A BUSINESS ENVIRONMENT AND ITS ROLE AND SIGNIFICANCE IN THE NATIONAL ECONOMY - Amanov Davron Ravshan ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
In the context of modern globalization and intensifying competition, the sustainable development of the national economy largely depends on the quality of the business environment. The business environment is a complex set of institutional, legal, financial, and organizational conditions created to ensure the free operation of entrepreneurial entities, attract investment, implement innovations, and promote effective competition through market mechanisms. Therefore, the formation and improvement of the business environment are considered one of the priority directions of national economic policy.